Pengembangan Aplikasi Mobile Untuk Digital Payment Pada Internet of Thing Coffee Vending Machine - Arfiandy; Heri Suroyo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Research has produced a Coffee Vending Machine (CVM) by developing an Android-based digital payment mobile application for CVM payment transactions. The digital payment transaction feature that has been developed using the Internet of Things (IoT) where users can make payments with CVM using a mobile application that can scan QR codes, After the user scans the QR code the server will process the transaction whether the balance that the user has is sufficient or not, if the balance is sufficient, the server will send a command to the CVM to issue a copy, the user's balance uses the balance that has been designed using a MySQL database. This research will use C, PHP and Java programming languages. This study uses a research method, namely the Research & Development (R&D) method and the development method used is the Unified Process Method.